Identification of Escherichia coli multidrug resistance transporters involved in anthocyanin biosynthesis - Wu, Xia; Chen, Rongxia; Liang, Ping; Zha, Jian (Frontiers in Microbiology, 2024)
The anthocyanin compound cyanidin 3-O-glucoside (C3G) is a natural pigment widely used in food and nutraceutical industries. Its microbial synthesis by E. coli is a promising alternative to the traditional extraction methods. However, part of the synthesized C3G accumulates in the cytoplasm, thus potentially causing growth inhibition and product degradation. Therefore, it is necessary to enhance C3G secretion via exploration of native transporters facilitating C3G export. In this study, we report the screening and verification of native multidrug resistance transporters from 40 candidates in E. coli that can improve the extracellular C3G production when using catechin as the substrate. Overexpression of single transporter genes including fsr, yebQ, ynfM, mdlAB and emrKY were found to increase C3G production by 0.5-to 4.8-fold. Genetic studies indicated that mdlAB and emrKY are vital transporters in the secretion of C3G. Our study reveals a set of new multidrug resistance transporters for the improvement of microbial biosynthesis of C3G and other anthocyanins.